Commitment of knowledge workers to their organizations: An evaluation of antecedents, levels and behavioral outcomes - Ismail, Zakaria; Omar, Abdullah (Universiti Utara Malaysia, 2006)
Globalisation has broaden the horizon of operations for many corporate organisations or business firms or public organisations which aspire to acquaint themselves with other global players.This is where the commitment and competency of their workforce are of paramount important that the management has to consider them seriously.It is vital as their competitiveness is contingent on this precious asset, by virtue of its exclusiveness, where ‘people’ cannot be copied easily.The ‘people’ is and would always be at the centre stage, particularly under the present construct of the emerging knowledge-based economies around the globe.The performance of the leading economies of the world, like the US, UK, Japan, Germany and other emerging economies in Asia, such as China and India will be very much depending on the merit and ability of their workforce to surge the challenges ahead.In this instance, knowledge workers’ expertise, contributions and commitments are extremely important.They have to be nurtured, managed and taken care of their issues correctly and adequately. Hence, it is important for organizations to know the special needs and motivations of knowledge workers if they are to successfully utilize their skills and retain them in the organization. This paper examined the influence of selected antecedents (professional commitment, job autonomy, traditional retention strategies, career planning, job opportunity, job satisfaction and learning opportunity) on three types of organizational commitment: affective, continuance and normative.For this purpose, a total number of 350 questionnaires were distributed to computer and IT specialists who are serving in the organizations that spearheaded computer and IT research and development in Malaysia.Only 191 questionnaires were returned (a response rate of 55 percent) and used for further analyses.Correlation analysis indicated that affective commitment was significantly correlated with career planning (negative), traditional retention strategies (negative) and learning opportunity (negative), while continuance and normative commitments were not correlated with any of the antecedents.Regression analyses indicated that affective commitment was positively affected by job satisfaction, and continuance commitment by traditional retention strategies (positive), career planning and (positive) and job autonomy (negative). Normative commitment was only positively affected by job satisfaction.The intention to leave was significantly and negatively correlated with all forms of the organizational commitment.The report also discussed implications of the study to human resource management practices and future direction of research in this area.